Weight prioritized slicing based on constraint logic programming for fault localization - Ren, Shengbing; Zhou, Weijia; Zhou, Haiwei; Xia, Lei (PloS one, 2020)
Fault localization, a technique to fix and ensure the dependability of software, is rapidly becoming infeasible due to the increasing scale and complexity of multilingual programs. Compared to other fault localization techniques, slicing can directly narrow the range of the code which needed checking by abstracting a program into a reduced one by deleting irrelevant parts. Only minority slicing methods take into account the fact that the probability of different statements leading to failure is different. Moreover, no existing prioritized slicing techniques can work on multilingual programs. In this paper, we propose a new technique called weight prioritized slicing(WP-Slicing), an improved static slicing technique based on constraint logic programming, to help the programmer locate the fault quickly and precisely. WP-Slicing first converts the original program into logic facts. Then it extracts dependences from the facts, computes the static backward slice and calculates the statements' weight. Finally, WP-Slicing provides the slice in a suggested check sequence by weighted-sorting. By comparing it's slice time and locate effort with three pre-exsiting slicing techniques on five real world C projects, we prove that WP-Slicing can locate fault within less time and effort, which means WP-Slicing is more effectively.